Al Majãz fī Syi’ri “Aurãqi al Zaitūni) li Maḥmūdi Darwīsy (Dirãsatun Taḥlīliyyatun fī ‘Ilmi al Bayãni) - Nafi’ah, Izza Kholisatun; Rosalinda, Rosalinda; Mahendra, Ahdiyat (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
Abstract:The purpose of this analysis is to find out what are the types of majaz contained in the awraaqun olive poem by Mahmoud Darwish dua to find out the alaqah and qarinah contained in the majaz in the awraaqun olive poem by Mahmoud Darwish. This research is a type of qualitative research by collecting data from books and other readings related to majaz. Data collection techniques using library techniques, listen and take notes. The data analysis technique uses flow analysis which consists of three activity flows that occur simultaneously, namely data reduction, data presentation, and drawing conclusions. While the source of data used in this research is in the form of documents, poetry awraaqun olive by Mahmoud Darwish in the form of soft files as many as 84 pages. This research is a balaghah analysis centered on the study of parrot science with one of the discussions being majaz. Majaz in the science of bayan there are two namely majaz lughawi and also majaz 'aqli. Majaz Lughawi itself discusses two issues, namely, the majaz 'isti'arah and alaqah of the majaz mursal itself including alaqatun sababiyyatun, alaqatun musababiyyatu, alaqatun haliyyatun, alaqatun juz'iyyatun, alaqah kuliyyah, alaqatun I'tibaru suddenly ma yakun. From the results of this analysis, the researchers found 14 sentences containing different majaz compositions according to the type of majaz itself, including 10 types of lughawi majaz which are divided into 4 types of majaz mursal, 2 types of majaz isti'arah and 4 types of majaz 'aqli.